Strategi Kampanye Public Relations Dinas Perhubungan Provinsi Jawa Barat Dalam Mensosialisasikan Program Diet Kendaraan Pribadi - Restia, Fasya Suci; Fuad, Ahmad (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2024)
This campaign aims to change people's behavior by encouraging public transportation, vehicle sharing, and adopting a sustainable lifestyle 1 This study adopts the Ostergaard Campaign Model as described by Venus (2019:1418), which consists of three main stages: (1) problem identification stage, (2) problem identification stage, (2) problem identification stage, and (2) problem identification stage.the management of the campaign, and (3) the evaluation stage. In the context of methodology, this study proposes a qualitative approach using descriptive methods. The results of this study illustrate that the Public Relations of the West Java Provincial Transportation Service has been practicing public relations campaigns regarding the Personal Vehicle Diet Program by complying with the approach stated in the Ostergaard Campaign Model. The first stage is problem identification, which includes high congestion problems, high levels of personal vehicle use, and low public awareness of public use. Furthermore, the second stage is campaign management involving design and implementation. Design involves internal evaluation and compilation of campaign content. The campaign was carried out in a face-to-face method through direct socialization and through Instagram social media. Finally, the third stage is an evaluation that includes an internal assessment of the effectiveness of the campaign that has been run.